An Intersectional Analysis of Ontario College Media Professors: Hiring and Careers, 1970s–1980s - Sianos, Helen (Ontario History, 2026)
This research analyzes the careers, teaching practices, and self-assessments of Ontario college media professors hired in the 1970s and 1980s in three parts of the province. I interviewed nine retired media professors and an academic manager about their professional experiences during the establishment of these programs. My historical account uses a feminist model of closure theory from the neo-Weberian sociology of professions, along with intersectional writing on identity, to explain the gendered and racialized nature of the labour market in these geographically and historcally specific areas during these years. How was hiring influenced by these elements?  At the beginning of this period, privileged white middle-class men with connections to education and industry experience founded the programs, eventually hiring privileged white women with relevant post secondary credentials and industry experience. However, not all the women hired in the 1980s began their careers full time, unlike their male colleagues, and those who did faced challenges within the institution.